Geographical immobility and local ancestral ties: a study of three generations of natives in Finland - Monti, Andrea; Saarela, Jan (Geografiska annaler. Series B, Human geography, 2025)
Research concerning internal migration has increasingly recognized family members outside the household as important factors for mobility decisions. Older generations and familiar environments constitute strong attractors thanks to location-specific capital and exchange of multigenerational support. Less is known about geographical immobility across generations. Wee study immobility patterns across three generations of native Finns by examining population register data that span over five decades. We analyse how geographical immobility in terms of a person’s place of residence at age 35 vs age 14 relates to the place of birth of their parents and grandparents. In this regard, Finland offers a highly useful case study because of its two main ethnolinguistic groups, Finnish and Swedish speakers, which are characterized by historically different mobility patterns and geographical concentrations. We find that geographical immobility relates strongly to local ancestral ties, that geographical immobility is much more common among Swedish than Finnish speakers, that the association between local ancestral ties and geographical immobility is stronger for Swedish than for Finnish speakers, and that it differs across geographical areas with different ethnolinguistic profiles. In terms of effect sizes, local ancestral ties have a large role in immobility behaviour, equally important as many socioeconomic and demographic factors.